Investigating the Anticonvulsant Properties of Aqueous Ethanolic Extracts of the Leaves, Roots, and Fruits of Jatropha gossypifolia L. (Euphorbiaceae) - Gideon Drafor; Emmanuel Duah; Nelson A. Ankamah; Godsway E. Kpene; Priscilla K. Mante (Advances in Pharmacological and Pharmaceutical Sciences)
Convulsion is a typical symptom associated with epilepsy. Jatropha gossypifolia, a common plant in Ghana, has been used traditionally for the management of epilepsy. This study was carried out to ascertain the scientific basis for the traditional utility of Jatropha gossypifolia for various convulsive disorders and also determine the part of the plant with the most anticonvulsant activity. The anticonvulsant activity of the leaf, root, and fruit extracts in doses of 30–300 mg/kg was assessed using the picrotoxin-induced seizure models in mice. The drugs and chemical preparations used included diazepam, picrotoxin, ethanol (70%), and normal saline. GraphPad Prism 6 was used for all statistical analysis and plotting of graphs. Data were analyzed using one-way ANOVA, followed by Bonferroni’s multiple comparison test. The leaf extract significantly and dose-independently reduced the frequency of myoclonic jerks (P=0.0001) and decreased the duration of clonic convulsions (P=0.019). The root extract also significantly and dose-dependently reduced the frequency of myoclonic jerks (P=0.001) but only decreased the frequency of tonic convulsions at 100 mg/kg (P=0.006). It also significantly decreased the duration of tonic convulsions (P=0.0001). The fruit extract only significantly and dose-independently reduced the frequency of myoclonic jerks (P=0.0001). It, however, showed an increase in the duration of both clonic and tonic convulsions. The study shows that the leaves and roots of Jatropha gossypifolia produce anticonvulsant activity which may be through enhancement of GABAergic transmission or activation of GABA receptors which support the traditional use of the plant to treat epileptic fits.